2019
DOI: 10.1007/s40279-019-01162-1
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Cramping During Exercise: Causes, Solutions, and Questions Remaining

Abstract: Muscle cramp is a temporary but intense and painful involuntary contraction of skeletal muscle that can occur in many different situations. The causes of, and cures for, the cramps that occur during or soon after exercise remain uncertain, although there is evidence that some cases may be associated with disturbances of water and salt balance, while others appear to involve sustained abnormal spinal reflex activity secondary to fatigue of the affected muscles. Evidence in favour of a role for dyshydration come… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
61
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 61 publications
0
61
0
2
Order By: Relevance
“…He had a doppler study [36] and an X-ray which revealed negative findings. His blood profile was unremarkable with normal findings in electrolyte values [11]. He was a recovering alcoholic and was on anti-depressants.…”
Section: Case Description History and Clinical Findingsmentioning
confidence: 97%
See 1 more Smart Citation
“…He had a doppler study [36] and an X-ray which revealed negative findings. His blood profile was unremarkable with normal findings in electrolyte values [11]. He was a recovering alcoholic and was on anti-depressants.…”
Section: Case Description History and Clinical Findingsmentioning
confidence: 97%
“…Individuals presenting to a primary care setting with lower leg, shin and calf pain are evaluated for the possible presence of blood clots [3], chronic exertional compartment syndrome (CECS) [4], stress fractures [5], and infrequently malignancy [6]. Other causes for lower leg and shin pain described in the literature are medial tibial stress syndrome (MTSS), popliteal artery entrapment syndrome (PAES) [7][8][9][10], peripheral neuropathy, lumbar radiculopathy, spinal stenosis [9,10], dehydration [11], vitamin B12 and vitamin D deficiency [12,13], exertional rhabdomyolysis [14], restless leg syndrome [15], varicosities [16], congestive cardiac failure [17] and renal pathology [18].…”
Section: Introductionmentioning
confidence: 99%
“…Hoffman and Stuemp e [4] demonstrated that overhydration was the primary characteristic of symptomatic hyponatremia during a 161-km running race. One of the symptoms of hyponatremia is muscle cramping, which is a painful, involuntary muscle contraction [5,6], and muscle cramp that occurrs during and/or following exercise is referred to as exercise-associated muscle cramp or EAMC [7][8][9]. It is possible that drinking a large amount of plain water dilutes sodium and other electrolytes in the blood and extracellular uid, increasing EAMC susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…Giuriato et al [13] have described that EAMC stems from an imbalance between excitatory drive from muscle spindles and inhibitory drive from Golgi tendon organs to the alpha motor neurons, rather than dehydration or electrolytes de cits. On the other hand, Maughan and Shirreffs [5] have stated in their recent review paper that high ambient temperature and large sweat losses accompanied by the ingestion of large volumes of plain water may be risk factors for EAMC. Therefore, it is interesting to examine the effects of plain water versus water containing electrolytes on EAMC to clarify whether any difference exists between the conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The initial two papers highlight areas relevant to athletic performance that are difficult to study—does hypohydration really impair endurance performance [1] and what causes muscle cramping [2]? In the former situation, how does the experimenter effectively blind the research subject from knowing their hydration status?…”
mentioning
confidence: 99%